P62 Drug induced hypothyroidism in patients receiving treatment for multi-drug resistant tuberculosis. (2nd December 2011) - Gupta, J; Breen, R A M; Milburn, H J
Abstract : Introduction and Objectives: Drug-induced hypothyroidism is an uncommon adverse effect of treatment for multi-drug resistant tuberculosis (MDR-TB), with a limited number of case reports from the 1950s reporting the issue. The most likely agents to cause hypothyroidism are p -aminosalicylic acid (PAS), and to a lesser extent Prothionamide, both commonly used in regimens to treat MDR-TB. We report five cases of MDR-TB, four of whom developed hypothyroidism while on treatment. This is the largest reported cohort to have developed drug-induced hypothyroidism as a result of MDR-TB treatment to date. We analysed if there were any predisposing or causative factors which may have contributed to patients developing hypothyroidism. Method: Patients were seen in clinic on a regular basis and possible adverse events evaluated by symptom review and clinical evaluation. Thyroid function tests (TFTs) were ordered based upon clinical suspicion. Following identification of hypothyroidism patients were started on thyroxine replacement therapy with monitoring of TFT levels to normalise them. Patient demographics were collected for analysis. Results: Four out of five patients (3 females and 1 male, aged 29–40 years) developed hypothyroidism following MDR-TB treatment with regimens containing PAS and Prothionamide. The dominant presenting symptom was lethargy, with one developing goitre and hair loss. All patients were from ethnic minorities born overseas in: India (1); Bangladesh (1) and Somalia (2). The 5 th female Nepalese patient remained euthyroid. Patients had been in the UK from 3 to 6 years with no travel history of note since. Hypothyroidism developed at varying stages of treatment from 101–442 days. On analysis of predisposing or causative factors for hypothyroidism development, those patients who originated from areas of iodine deficiency (eg, Bangladesh) developed hypothyroidism sooner after commencing treatment and took longer for euthyroid resolution despite receiving increased dosages of thyroxine replacement therapy. Conclusion: Individuals originating from areas of iodine deficiency have an increased likelihood of developing drug induced hypothyroidism when receiving a regimen containing PAS and/or Prothionamide for MDR-TB treatment. As symptoms of hypothyroidism were generally non-specific and could easily be ascribed to TB, we suggest monitoring TFTs in all patients on prolonged treatment regimens containing PAS and/or Prothionamide.